Proceedings of the 38th International Symposium on Automation and Robotics in Construction (ISARC) 2021
DOI: 10.22260/isarc2021/0031
|View full text |Cite
|
Sign up to set email alerts
|

A proof of concept application of sensing technologies for managing proximity hazards on construction sites

Abstract: Construction is among the most dangerous industries for the safety of workers. Due to the dynamism typical of construction sites, where workers, materials and equipment resources are often in motion, collisions and contact with moving construction machineries and heavy equipment represents one of the main safety problems. The study described in this paper concerns with the preliminary development of a proximity warning system (PWS) for construction activities, which is based on the implementation of sensing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Figure 1 depicts a typical UWB RTLS network architecture. Network nodes can be referred to as anchors, set up at fixed places, and tags, fastened to the moving objects that need to be tracked [ 8 ]. The node in charge of managing transmission timing between nodes and permitting new nodes to join the network is known as the network coordinator.…”
Section: Research Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1 depicts a typical UWB RTLS network architecture. Network nodes can be referred to as anchors, set up at fixed places, and tags, fastened to the moving objects that need to be tracked [ 8 ]. The node in charge of managing transmission timing between nodes and permitting new nodes to join the network is known as the network coordinator.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Unless solutions like GPS receivers with Real Time Kinematic (RTK) support are used, it is difficult to obtain these results using GPS technology. Moreover, the cost of these solutions would make them unsuitable for widespread use on construction sites [ 8 ]. On the other hand, studies have shown how the performance of UWB-based PWSs should be evaluated, taking into account aspects such as the error rate of real-time location tracking and the possible effects of non-line of sight [ 40 , 41 ].…”
Section: Research Backgroundmentioning
confidence: 99%
See 3 more Smart Citations